Diverse nanocomposites as a potential dressing for diabetic wound healing - Renuka, Remya Rajan; Julius, Angeline; Yoganandham, Suman Thodhal; Umapathy, Dhamodharan; Ramadoss, Ramya; Samrot, Antony V.; Vijay, Danis D. (Frontiers in Endocrinology, 2023)
Wound healing is a programmed process of continuous events which is impaired in the case of diabetic patients. This impaired process of healing in diabetics leads to amputation, longer hospitalisation, immobilisation, low self-esteem, and mortality in some patients. This problem has paved the way for several innovative strategies like the use of nanotechnology for the treatment of wounds in diabetic patients. The use of biomaterials, nanomaterials have advanced approaches in tissue engineering by designing multi-functional nanocomposite scaffolds. Stimuli-responsive scaffolds that interact with the wound microenvironment and controlled release of bioactive molecules have helped in overcoming barriers in healing. The use of different types of nanocomposite scaffolds for faster healing of diabetic wounds is constantly being studied. Nanocomposites have helped in addressing specific issues with respect to healing and improving angiogenesis.